Leveraging data for policy change: A descriptive analysis of Latino men’s postsecondary enrollment and degree attainment patterns in Texas - Burmicky, Jorge; Ryu, Wonsun; Palomín, Leticia; Sáenz, Victor B. (Education Policy Analysis Archives, 2022)
This study examines the educational outcomes of Latino men in Texas by conducting a descriptive policy-focused disaggregate analysis of longitudinal data from the 8th Grade Cohort Longitudinal Study and the Integrated Postsecondary Data System (IPEDS). Based on our analysis, we provide context and understanding of the progress made towards meeting the goals set forth in 60x30TX, a statewide higher education plan led by the Texas Higher Education Coordinating Board. Our findings reveal educational equity disparities by looking at the postsecondary enrollment and degree/certificate completion patterns of Latino men in Texas. In addition, we provide an analysis of differences in educational equity disparities across various regions of the state. We share policy planning implications informed by practitioner input to better contextualize our findings.